AKROTHINIA 2 Contributi di giovani ricercatori agli studi egei e ciprioti - ALBERTI, MARIA EMANUELA; Jasink, Anna Margherita (Strumenti per la didattica e la ricerca, 2018)
Akrothinia 2 presents itself as a sequel to Akrothinia, which appeared three years ago in this same series, and aims at providing an overview of the research young scholars carried out in the field of Prehistory and Protohistory of the Aegean Sea area. Compared to the previous volume, there is the new inclusion of some essays by young foreign scholars, who have spent periods of study at Italian institutes during their preparation, thus creating an international link from the beginning of their scientific activity. It is now increasingly clear that Aegean studies, mainly focused on the two great Minoan and Mycenaean civilizations, represent a junction point between the general pre-classical Mediterranean world and the subsequent Greek one.